Intra-Department Model of University Teacher’s Motivation Management - E. G. Gutsu; Yu. Yu. Chilipenok (Высшее образование в России, 2019)
In the context of reforming higher education, the problem of developing and implementing a new, effective management policy aimed at attracting, retaining and motivating highly qualified scientific and pedagogical personnel is of particular relevance. However, as noted in a number of studies, university teachers find themselves in a difficult situation, which is caused by a decline in public recognition of the profession value, staff shortages, turnover and aging of staff, a crisis of motivationand professional identity in higher education amid significant complications in professional activities. The current stage of higher education development is characterized by large-scale innovation processes, therefore, management of the motivation of teachers of higher education institutions should be considered as the management of motivation in the context of innovation. The basis of this approach is an orientation on creativity and stimulation of personnel’s innovative behavior. It is obvious that the task of effective management of university teachers’ motivation should be solved as soon as possible, without interrupting the professional activities and within the working teams. The article presents the experience of developing and testing a layered model of intra-departmental management of university teachers’ motivation, which is based on the idea of forming a motivated team and creating a corporate culture that will help effectively manage innovative processes at the university.